2011
DOI: 10.1093/ndt/gfr510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of regional citrate anticoagulation in liver transplant patients requiring post-operative renal replacement therapy

Abstract: Regional citrate anticoagulation for CRRT in the early post-operative period after liver transplantation is effective and safe. Therefore, the general exclusion of citrate anticoagulation during CRRT in patients after liver transplantation is not justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
1
48
0
1
Order By: Relevance
“…Safety of citrate versus unfractionated heparin has been recently demonstrated for continuos RRT (15,16), and confirmed in high hemorrhagic risk AKI patient categories, such as those liver dysfunction (38)(39)(40)(41), burns with septic shock (42), and heart surgery (43). Two major issues of our approach deserve discussion: the hemorrhagic risk and the complications associated with citrate accumulation.…”
Section: Discussionmentioning
confidence: 94%
“…Safety of citrate versus unfractionated heparin has been recently demonstrated for continuos RRT (15,16), and confirmed in high hemorrhagic risk AKI patient categories, such as those liver dysfunction (38)(39)(40)(41), burns with septic shock (42), and heart surgery (43). Two major issues of our approach deserve discussion: the hemorrhagic risk and the complications associated with citrate accumulation.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the Canadian Society of Nephrology commentary on these KDIGO guidelines endorsed this statement, suggesting the possibility of cautiously extending RCA use in patients with relative contraindications for citrate (21). In this regard, the adoption of well designed RCA protocols, characterized by reduced citrate load and careful monitoring, could permit safe delivery of RCA in patients with severely impaired liver function and/or shock with tissue hypoperfusion (47,53,(56)(57)(58). Moreover, although the incidence of metabolic and/or electrolyte disorders with RCA is low, operational parameters and combinations of different CRRT solutions with either isotonic or hypertonic citrate formulations may significantly affect electrolyte and buffer balance during RCA.…”
Section: Discussionmentioning
confidence: 99%
“…Close attention to the early signs of citrate accumulation is mandatory in high-risk patients (21); in particular, because the main risk of citrate accumulation is a rapid fall in the systemic ionized calcium level, potentially resulting in serious complications, such as hypotension and arrhythmias (10,52), the usual calcium monitoring intervals (4-6 hours) as well as the timing of the calcium ratio assessment should be shortened in patients who may have impaired citrate metabolism (e.g., those with severe liver failure and tissue hypoperfusion). Despite these concerns, there is increasing evidence of the safety of RCA in patients with severe liver failure/liver transplant with or without molecular adsorbent recirculating system support (53,(56)(57)(58) or severe septic shock with liver hypoperfusion (47). In these clinical settings, strategies for the prevention of citrate accumulation should be targeted to reduce the citrate load by decreasing citrate administration (lower blood flow rates and higher ionized calcium targets) and/or increasing citrate clearance (higher convective and/or diffusive dialysis dose) (59).…”
Section: Citrate Accumulation Risk and Rca Monitoringmentioning
confidence: 99%
“…The authors concluded that citrate anticoagulation can be performed in patients with decompensated cirrhosis provided there is citrate dose adjustment and careful monitoring of iCa 2+ . Saner et al [7] evaluated the safety and efficacy of citrate in 68 liver transplant recipients who developed postoperative acute kidney injury requiring CRRT. Median duration on CRRT was 8 days (range 1–39 days) and mean circuit life was 22.76 ± 14.6 h. There was no relevant trend of serum sodium, potassium, calcium, bicarbonate, or pH values during use of CRRT.…”
Section: Metabolic Acidosismentioning
confidence: 99%